PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT LESTARI MANDIRI ERAJAYA DI APARTEMEN GADING NIAS RESIDENCE KELAPA GADING JAKARTA UTARA - Muhammad Fahrul Alam; Muhammad Gandung (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of workload and work environment on employee performance at PT Lestari Mandiri Erajaya North Jakarta both partially and simultaneously. The research method used is quantitative which is associative. The sampling technique uses a saturated sample technique totaling 65 employees. Data collection techniques through primary and secondary data. The results of the study indicate that there is a significant positive effect between workload and employee performance, with a correlation value of 0.758 and a determination value of 71.2%, while 28.8% is influenced by other factors. Hypothesis testing shows that t count (5.341) is greater than t table (1.999) and the Sig. value (0.000) is less than 0.05, so H01 is rejected and Ha1 is accepted. Furthermore, the study also found a significant positive effect between work environment and employee performance, with a correlation of 0.703 and a contribution of 79.5%. Hypothesis testing shows t count (7.853) is greater than t table (1.999) and the Sig. value. (0.000) is less than 0.05, so H02 is rejected and Ha2 is accepted. In addition, there is a simultaneous positive influence between workload and work environment on employee performance, with the regression equation Y = 10.258 + 0.251 X1 + 0.546 X2. The correlation coefficient value of 0.720 and the determination coefficient of 71.9% indicate a strong relationship. Hypothesis testing shows that Fcount (33.395) is greater than Ftable (3.15) and the Sig. value (0.000) is less than 0.05, so H03 is rejected and Ha3 is accepted. This finding confirms that both workload and work environment contribute significantly to improving employee performance at PT Lestari Mandiri Erajaya North Jakarta.